Zoophagic behaviour of anopheline mosquitoes in southwest Ethiopia: opportunity for malaria vector control. Issue 1 (December 2015) - Massebo, Fekadu; Balkew, Meshesha; Gebre-Michael, Teshome; Lindtjørn, Bernt
Abstract Background Increased understanding of the feeding behaviours of malaria vectors is important to determine the frequency of human-vector contact and to implement effective vector control interventions. Here we assess the relative feeding preferences ofAnopheles mosquitoes in relation to cattle and human host abundance in southwest Ethiopia. Methods We collected femaleAnopheles mosquitoes bi-weekly using Centers for Disease Control and prevention (CDC) light traps, pyrethrum spray catches (PSCs) and by aspirating from artificial pit shelters, and determined mosquito blood meal origins using a direct enzyme-linked immunosorbent assay (ELISA). Results BothAnopheles arabiensis Patton andAn. marshalli (Theobald) showed preference of bovine blood meal over humans regardless of higher human population sizes. The relative feeding preference ofAn. arabiensis on bovine blood meal was 4.7 times higher than that of human blood.Anopheles marshalli was 6 times more likely to feed on bovine blood meal than humans. The HBI ofAn. arabiensis andAn. marshalli significantly varied between the collection methods, whereas the bovine feeding patterns was not substantially influenced by collection methods. Even though the highest HBI ofAn. arabiensis andAn. marshalli was from indoor CDC traps collections, a substantial number ofAn. arabiensis (65 %) andAn. marshalli (63 %) had contact with cattle.Anopheles arabiensis (44 %) andAn. marshalli (41 %) had clearly taken bovine blood meals outdoors, but they rested indoors. Conclusion Anopheles mosquitoes are zoophagic and mainly feed on bovine blood meals than humans. Hence, it is important to consider treatment of cattle with appropriate insecticide to control the zoophagic malaria vectors in southwest Ethiopia. Systemic insecticides like ivermectin and its member eprinomectin could be investigated to control the pyrethroid insecticides resistant vectors.